1996
DOI: 10.1111/j.1939-1676.1996.tb02065.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of the Common Bile Duct in Cats

Abstract: Ultrasound is an excellent imaging tool in the evaluation of the biliary tract in cats. Extrahepatic obstruction could be diagnosed by the presence of dilated common bile duct (CBD), which was measured ventral to the portal vein in the porta hepatis. At this level, the diameter of the CBD in 6 holestatic hepatic disease is common in cats.' The spe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 12 publications
(2 reference statements)
4
94
0
1
Order By: Relevance
“…1,[51][52][53] In the present study, abnormalities suggestive of EHBTO were found in all 21 cats that underwent ultrasonography. Because chronic biliary obstruction can itself result in irreversible inflammatory and fibrotic changes, 48-50 more timely diagnosis of EHBTO might improve the clinical outcome in affected cats.…”
Section: Discussionmentioning
confidence: 73%
“…1,[51][52][53] In the present study, abnormalities suggestive of EHBTO were found in all 21 cats that underwent ultrasonography. Because chronic biliary obstruction can itself result in irreversible inflammatory and fibrotic changes, 48-50 more timely diagnosis of EHBTO might improve the clinical outcome in affected cats.…”
Section: Discussionmentioning
confidence: 73%
“…5 The literature describing ultrasonographic changes to the CBD in non-obstructive processes reports less severe CBD dilatation. In a population of cats with surgical or necropsy-confirmed non-obstructive hyperbilirubinemia, maximal CBD diameter did not differ significantly from normal cats, 4 and in cats with cholangitis or liver fluke infestation CBD dilatation to or beyond 5 mm was not reported in conjunction with a patent biliary tract. 9,14,15 …”
Section: Introductionmentioning
confidence: 68%
“…1,2 The remaining components of the biliary tree (extrahepatic ducts and intrahepatic structures, including interlobular ducts, interlobar ducts and larger hepatic bile ducts) are not ultrasonographically visible unless there is pathological dilatation. 1,2,4 In the cat, a CBD diameter of up to 4 mm is considered normal. 2,4,5 …”
Section: Introductionmentioning
confidence: 99%
“…A vesícula biliar preservou caracterís-ticas conforme citações entre as espécies domésticas . Apresentou-se sempre repleta e com conteúdo anecói-co, não demonstrando assim, indícios de doença do sistema biliar, bastante comum nas visualizações da vesícula biliar para algumas espécies primatas (Pissinatti et al 1992), carnívoros (Léveillé et al 1996) e mesmo no homem (Shea et al 1994, Pandey et al 1996, Petroni et al 2000.…”
Section: A C Bunclassified